Dilly And The School Play - "Bradman, Tony" (Egmont Books: London, 2002)
Dilly is a very talented dinosaur. So when he hears about the school play, Dilly just knows he will be the show's star. But his play has plenty of surprises! Suggested level: primary
Keywords: Schools Fiction